2009
DOI: 10.1017/s0967199408004991
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic preservation of embryos ofProchilodus lineatus(Valenciennes, 1836) (Characiforme; Prochilodontidae)

Abstract: SummaryWhile the freezing techniques of mammal embryos have been providing promising results, the cryopreservation of teleostean eggs and embryos have remained unsuccessful up to now. Therefore, this work aimed to develop a procedure of cryogenic preservation of embryos of Prochilodus lineatus and to observe, at both structural and ultrastructural levels, the morphological alterations that took place after the application of freezing/thawing techniques. The embryos at the morula stage could not tolerate exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…However, temperature sensitivity is variable and dependent upon species, tissue, and cell characteristics and embryonic stage (Dinnyés et al, 1998;Ninhaus-Silveira et al, 2008).…”
Section: E170043[2]mentioning
confidence: 99%
See 2 more Smart Citations
“…However, temperature sensitivity is variable and dependent upon species, tissue, and cell characteristics and embryonic stage (Dinnyés et al, 1998;Ninhaus-Silveira et al, 2008).…”
Section: E170043[2]mentioning
confidence: 99%
“…In order to maximize performance and reduce toxic effects, many studies have sought increased permeability of tissues and embryonic cells to cryoprotectants, reducing their concentration and diffusion time and hence, the dehydration period of biological material (Suzuki et al, 1995;Ninhaus-Silveira et al, 2008;Robles et al, 2009). One solution adopted for some species is removal or permeation of the chorionic membrane with enzyme solutions (Robles et al, 2003;Ninhaus-Silveira et al, 2008).…”
Section: E170043[2]mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique does not constitute an effective protocol, mainly because of the difficulties in developing substances that penetrate the chorionic sac and protect the embryo from formation of intracellular ice crystals during the procedure (Kusuda et al, 2002;Ninhaus-Silveira et al, 2009). Although Hagedorn et al, (1996) observed in images by magnetic resonance that methanol permeated the entire zebrafish embryo within 15 min and propylene glycol and dimethyl sulfoxide exhibited little or no penetration over 2.5 h and considered that the yolk syncytial layer may be selectively permeable to specific charges or conformations.…”
Section: Introductionmentioning
confidence: 99%
“…For zebrafish (Brachydanio rerio), 2M methanol proved to be more effective and less toxic (Zhang et al, 1993). For curimba, 1.5 M of dimethyl sulfoxide and propylene glycol proved to be less toxic, promoting the highest percentage of survival (78.95%) after toxicity assays, but no embryos survived after cryopreservation (Ninhaus-Silveira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%